2017
DOI: 10.1021/acs.langmuir.7b01485
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Microgels for the Selective Separation of Halogen Compounds from Aqueous Solution

Abstract: Nanocomposite microgels that selectively adsorb and release halogen compounds were developed. These nanocomposite microgels consist of poly(2-methoxyethyl acrylate) (pMEA) and a poly(oligo ethylene glycol methacrylate) hydrogel matrix. Therefore, the methoxy groups of the former are crucial for the halogen bonding, while the presence of the latter adds colloidal stability and allows controlled uptake/release of the halogen compounds. Such nanocomposite microgels may not only be used as dispersed carriers, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…In our previous studies on pMEA composite microgels, the chain length of the ethylene oxides in the thermoresponsive pOEG gel matrix (five or six carbon atoms) played an important role for the temperature-dependent release of RB. 21…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies on pMEA composite microgels, the chain length of the ethylene oxides in the thermoresponsive pOEG gel matrix (five or six carbon atoms) played an important role for the temperature-dependent release of RB. 21…”
Section: Resultsmentioning
confidence: 99%
“…1519 We found that polymer microspheres selectively adsorb and release halogen compounds. 20,21 These microspheres consist of hydrophobic poly(2-methoxyethyl acrylate) (pMEA) and a poly(oligo(ethylene glycol) methacrylate) hydrogel matrix, i.e., they represent polymer/polymer composite hydrogel microspheres (microgels). These microgels benefit from not only the aforementioned microsphere features but also the intrinsic features of the hydrogel network, which allows halogen compounds to enter the inside of the microgels via diffusion and to exit the microgels upon applying external stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of a typical microgel is in the range of several tens of nanometers to several micrometers, and thus, microgels can respond instantly to external stimuli such as changes in temperature, pH, and solvent. Due to their desirable properties, microgels have found applications, not only in a dispersed state, for example as carriers for drug-delivery systems, [5][6][7] in molecular separations, [8][9][10][11] and in functional catalysts, [12][13][14] but also in assembled states, for example as cell scaffolds, 15,16 sensors, 17,18 emulsi-ers, 19,20 and actuators. [21][22][23] The rst reported microgels were thermoresponsive poly(Nisopropyl acrylamide) (pNIPAm)-based microgels cross-linked with N,N 0 -methylenebis(acrylamide) (BIS).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] They can also be used in biosensing applications, 12 as nano or microreactors with tuneable catalytic reaction rates 13,14 or as selective traps for chemical separation and purification. 15,16 Of particular interest to some applications are stimuli-responsive hollow hydrogels: particles formed by a single or multiple cross-linked polymeric shells with a hole inside, in which the swelling of the polymeric network may be varied, for instance, with temperature of solvent pH. [17][18][19][20] On the one hand, the presence of the internal void greatly enhances the load capacity of different kind of molecules (drugs, proteins and other biomolecules, reactants,...) [21][22][23][24] On the other hand, by tuning the swelling state of the hydrogel membrane, the diffusion process and, consequently, the cargo encapsulation/release rate, can be externally manipulated.…”
mentioning
confidence: 99%